Behaviors of Deformation, Recrystallization and Textures Evolution of Columnar Grains in 3%Si Electrical Steel Slabs - SHAO Yuan-yuan; GUO Qi (Cailiao gongcheng, 2017)
The behaviors of deformation and recrystallization and textures evolution of 3% (mass fraction) Si columnar-grained electrical steel slabs were investigated by electron backscatter diffractometer technique and X-ray diffraction. The results indicate that the three columnar-grained samples have different initial textures with the long axes arranged along rolling, transverse and normal directions. Three shear orientations can be obtained in surface layer after hot rolling, of which Goss orientation is formed easily. The α and γ fibre rolling orientations are obtained in RD sample, while strong γ fibre orientations in TD sample and sharp {100} orientations in ND sample are developed respectively. In addition, cube orientation can be found in all the three samples. The characteristics of hot rolled orientations in center region reveal distinct dependence on initial columnar-grained orientations. Strong {111}〈112〉 orientation in RD and TD samples separately comes from Goss orientation of hot rolled sheets, and sharp rotated cube orientation in ND sample originates from the initial {100} orientation of hot rolled sheets after cold rolling. Influenced by initial deviated orientations and coarse grain size, large orientation gradient of rotated cube oriented grain can be observed in ND sample. The coarse {100} orientated grains of center region in the annealed sheets show the heredity of the initial columnar-grained orientations.